TOTAL NEW HIV INFECTIONS IN PHILIPPINES A BOX-JENKINS ARIMA APPROACH (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
While HIV infections have declined globally, in the Philippines it is the opposite. The Philippines has an alarming number of new HIV infections (Senate of the Philippines, 2018). Using annual time series data on the total number of new HIV infections in Philippines from 1990 – 2018, the study makes predictions for the period 2019 – 2030. The study applies the Box-Jenkins ARIMA approach. The diagnostic ADF tests show that, E, the series under consideration is an I (2) variable. Based on the AIC, the study presents the ARIMA (0, 2, 2) model as the optimal model. The diagnostic tests further reveal that the presented model is quite stable and its residuals are not serially correlated. The results of the research indicate that the total number of new HIV infections in Philippines, will over the out-of-sample, increase by a staggering 87% rate